Fractal Dimension Option Hedging Strategy Implementation During Turbulent Market Conditions in Developing and Developed Countries - L.J. Basson; Sune Ferreira-Schenk; Zandri Dickason-Koekemoer (International Journal of Economics and Financial Issues, 2022)
A hedging strategy is designed to increase the likelihood of desired financial outcomes. Market speculators hedge investment positions if they are worth protecting against potential negative outcomes of turbulent market conditions and effective hedging implementation can reduce the impact severity on the underlying investment since these negative scenarios cannot be avoided. This paper provides a solution for investors to implement a trading strategy to effectively manage turbulent market conditions (such as the COVID pandemic) by implementing an investment trading approach. The investment strategy includes an index held by the investor (long position) and uses a fractal dimension indicator to warn when liquidity or sentiment changes are imminent within financial markets. When the threshold is breached at a predetermined level, the investor will take this observation as a change in liquidity in the market and a hedging position is undertaken. This sequence of events triggers the implementation of a hedging strategy by entering a buy put option position. The fractal indicator was found to be effective when applied to four of the six tested indices in terms of cumulative returns, but also in effect increased the risk taken by the investor for all six indices. The conclusion was made that where the outcome was similar for each economy type, both had a scenario where two out of the three economies outperformed the underlying index and had one index not outperforming the underlying index. This comparison was done to establish whether the hedging strategy had a more promising application to a developing or developed economy type. The fractal indicator was found to be effective when applied to four of the six tested indices in terms of cumulative returns, but also in effect increased the risk taken by the investor for all six indices.